Les limites d’une politique de replantation en pays bocager - Aurélie Javelle (Territoire en Mouvement)
A study in ecological anthropology focused on the reasons to maintain a local traditional practice of trees management on fields borders, in N-E Brittany, France. While the study illustrates farmers don't want to perpetuate this organisation, it also shows the need to think about the cohabitation of the older trees with new hedgerows planted thanks to official programmes. These hedgerows may be chosen for aesthetic reasons or transformed in combustible in the context of sustainable energies development programmes. This new solution is presented by various organisms as a solution to save or even redevelop the « bocage » thanks to a sustainable management. Farmers do not look like sharing this idea they are not used to, and that comes from organims that do not share their cultural values. Then, the goals of the various actors that manage the landscape never meet each other. Furthermore, the programmes are based on the opposition of an old bocage with positive connotation to a new one with negative connotations, in order to justify goals created through the vision of an idealized old « bocage ». This dismal continuity is the basis of a policy declared sustainable, but that cannot meet the local actors expectations, and that, this way, creates its own limits. Any sustainable intervention must then know and take into account the surrounding –here ecological and social– where it takes place.